Evaluation of Traffic Congestion in an Urban Roads: A Review - SUBAIR, Sulaiman Olayinka; IBITOYE, Biliyamin Adeoye; KURANGA, Abdulrauf Toyin (ABUAD Journal of Engineering and Applied Sciences, 2024)
Urban traffic congestion significantly impacts economic productivity, environmental health, and residents' quality of life. This study provides a comprehensive evaluation of traffic congestion in urban areas, focusing on recent innovations in traffic management, urban planning, public transportation, and technological advancements. Intelligent Transportation Systems (ITS), incorporating real-time data and adaptive signal controls, have proven effective in reducing delays and improving traffic flow. The study underscores the importance of mixed-use urban planning in minimizing travel distances and traffic volumes. Expanding public transportation networks is highlighted as a critical strategy for alleviating congestion, with evidence indicating that cities with extensive transit systems experience lower congestion levels. Additionally, the environmental and health implications of traffic congestion are considered, linking high congestion levels to increased pollution and negative health outcomes. . Road construction as a policy intervention to reduce congestion is debated, with the understanding that road widening may sometimes increase traffic. Evaluating the technologies contributing to congestion is crucial for devising effective solutions. Urban transport is central to economic activity and the well-being of urban residents. The rising population and car ownership rates, coupled with unchanged natural land areas, exacerbate traffic issues, leading to accidents and increased carbon dioxide emissions. The article explores the complexities of urban road traffic, addressing transport infrastructure, organization, and the high share of car traffic. It discusses theoretical and practical aspects of traffic flow and design, as well as the role of driver behavior in traffic jams.